Teacher’s Dilemma during Distance Learning: Work or/and Family? (The Important of Work Family Conflict Self-Efficacy and Spouse Support) - Luh Putu Ratih Andhini; Ni Made Sintya Noviana Utami (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
The purpose of the study is to find out the correlation between work-family conflict self-efficacy and spouse support work-family conflict. The writer used a quantitative approach to 150 teachers in Denpasar during the Distance Learning which is taken by fulfilling the purposive random system criteria. The instrument work-family conflict scale that had been used, the work-family conflict self-efficacy scale, and the spouse support scale which is already valid and reliable and spreading online. The double regression analysis has been used in this study to process the data. The results are R square = 0.176, Sig. = 0.000 < α, which means there is a correlation between the two independent variables simultaneously to the dependent variable. T-test found that Beta = -0.419; Sig. = 0.007 < α (there is a correlation between work-family conflict self-efficacy to work-family conflict), meanwhile spouse support variable found Beta = -0.004; Sig. = 0.957 > α (there is no correlation between spouse support to work-family conflict). The importance of this study for the teachers that never get support and do not have any self-confidence to process the conflict will give an impact on their mental health such as high-stress levels. Besides that, it can cause domestic violence. Tujuan penelitian adalah untuk mengetahui hubungan antara efikasi diri konflik kerja keluarga dan dukungan pasangan terhadap konflik kerja keluarga. Peneliti menggunakan pendekatan kuantitatif pada 150 tenaga pendidik di Denpasar selama pembelajaran jarak jauh (PJJ) yang diambil dengan cara purposive random memenuhi kriteria. Instrumen yang digunakan skala work family conflict, skala work family conflict self-efficacy, dan skala dukungan pasangan yang sudah valid dan reliabel dan disebarkan secara online. Analisis regresi ganda digunakan dalam penelitian ini untuk mengolah data. Hasil yang diperoleh Rsquare=0.176, Sig.=0.000<α, artinya terdapat hubungan antara kedua variabel bebas secara bersamaan terhadap variabel terikat. Uji t diperoleh Beta=-0.419; Sig.=0.007<α (ada hubungan efikasi diri konflik kerja keluarga terhadap konflik kerja keluarga), sedangkan variabel dukungan pasangan diperoleh nilai Beta=-0.004; Sig.=0.957>α (tidak ada hubungan dukungan pasangan terhadap konflik kerja keluarga. Pentingnya penelitian bagi tenaga pendidik yang tidak mendapatkan dukungan dan tidak memiliki keyakinan diri mengelola konflik akan berdampak pada kesehatan mental seperti memiliki tingkat stres tinggi. Selain itu, dapat menyebabkkan kekerasan dalam rumah tangga.